2020
DOI: 10.1038/s41598-020-60673-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the HSP101/CLPB gene family for heat tolerance in hexaploid wheat

Abstract: Heat Shock Protein 101 (HSP101), the homolog of Caseinolytic Protease B (CLPB) proteins, has functional conservation across species to play roles in heat acclimation and plant development. In wheat, several TaHSP101/CLPB genes were identified, but have not been comprehensively characterized. Given the complexity of a polyploid genome with its phenomena of homoeologous expression bias, detailed analysis on the whole TaCLPB family members is important to understand the genetic basis of heat tolerance in hexaploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 83 publications
1
11
0
Order By: Relevance
“…Once infected by the aforementioned fungal pathogen, B and D homoeologs exhibit stronger responses to the infection than A homoeologs, which implies distinctions of homoeolog expression bias under different biotic and abiotic stresses in many resynthesized or natural hybrids. Indeed, some recent studies have also revealed that the expression levels of certain homoeologous genes are altered under heat tolerance, water stress, and iron deficiency in polyploid wheat 48 50 . Hence, homoeolog expression bias of pods and seeds of Raphanobrassica under different stresses still remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Once infected by the aforementioned fungal pathogen, B and D homoeologs exhibit stronger responses to the infection than A homoeologs, which implies distinctions of homoeolog expression bias under different biotic and abiotic stresses in many resynthesized or natural hybrids. Indeed, some recent studies have also revealed that the expression levels of certain homoeologous genes are altered under heat tolerance, water stress, and iron deficiency in polyploid wheat 48 50 . Hence, homoeolog expression bias of pods and seeds of Raphanobrassica under different stresses still remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…7 ). In wheat, the P-loop motifs were found to be important components of the heat shock protein that confers heat tolerance (Erdayani et al 2020 ). In Arabidopsis, the P-loop protein was highly expressed in shoot meristems and was involved in the enhancement of cell division via regulating the reactive oxygen species (ROS) homeostasis (Yu et al 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…These include: transcripts encoding several HSP70 and HSP40 proteins that form DnaK–DnaJ complexes involved in exposing damaged proteins to disaggregation by high‐molecular‐weight chaperones (Haq et al, 2019); REVEILLE ( RVE ), HEAT SHOCK FACTOR ( HSF ), FCA and ETHYLENE RESPONSIVE FACTOR ( ERF ) genes known to interact in the thermotolerance pathway of A . thaliana (Erdayani et al, 2020; Lee et al, 2014; Li et al, 2019); and FT , which is a highly conserved florigen that promotes flowering (Wickland & Hanzawa, 2015). Conversely, microtubule‐related genes (e.g., MICROTUBULE ASSOCIATION PROTEIN 65 ‐like [ MAP65 ]; MC7G113600) were specifically down‐regulated at 40°C, which is interesting given that low‐temperature stress signalling and response have been linked to changes in membrane fluidity and cytoskeletal reorganization, respectively (Ma & Liu, 2019; Nick, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Different letters indicate significant differences between groups based on two-tailed post hoc Tukey tests (p < .01). Thin coloured lines join the means for plants within the same maternal family; thick black lines join the median for all plants, with violin plots showing the distribution of family mean RGR and ETHYLENE RESPONSIVE FACTOR (ERF) genes known to interact in the thermotolerance pathway of A. thaliana (Erdayani et al, 2020;Lee et al, 2014;Li et al, 2019); and FT, which is a highly conserved florigen that promotes flowering (Wickland & Hanzawa, 2015). Conversely, microtubule-related genes (e.g., MICROTUBULE ASSOCIATION PROTEIN 65-like [MAP65]; MC7G113600) were specifically down-regulated at 40°C, which is interesting given that low-temperature stress signalling and response have been linked…”
Section: Scarlet Monkeyflowers Have the Potential To Rapidly Adapt To...mentioning
confidence: 99%